Informal sport spaces as beacons of social cohesion: a case study of informal sport in “Chicago,” Western Cape, South Africa - Horn, Anele; Marais, Willis (Frontiers in Human Dynamics, 2025)
This paper presents research conducted in an informal settlement in Paarl, Western Cape (South Africa). The research demonstrates the importance of team sport activities as an instrument to encourage community cohesion. It does this by demonstrating how sport facilities are planned for and provided in low income communities, and what the challenges are with regards to the provision, accessibility and maintenance of such facilities. A mixed methods approach consisting of policy analysis, spatial analysis, focus group discussions and semi structured interviews formed the basis of the research methodology. The results indicate that while policies exist to provide for sport and recreation in lower income communities, financial, institutional and logistical challenges cause these facilities to fall short in terms of communities’ requirements. However, the importance of sport both as participants and spectators have been recognised by community members themselves, consequently leading to the utilisation of informal spaces as community-driven informal sport venues.